Analyses of the physicochemical and sensory characteristics of black goat triceps brachii muscle based on slaughter age - Sol-Hee Lee; Hack-Youn Kim (Food Chemistry: X)
In this study, we aimed to analyze the effects of slaughter age on black goat meat's physicochemical and nutritional characteristics. Goats (age: 3, 6, 9, 12, 24, and 36 months) reared under identical conditions were used in this study. The key parameters were analyzed, including color, cooking yield, shear force, free amino acid (FAA) levels, free fatty acid levels, and sensory attributes. Hue values decreased, whereas redness increased with age. Umami and sweet FAA levels increased with age, and bitter FAA levels increased from 9 months. The flavor scores increased with age up to 9 months. Off-flavors were significantly higher in goats aged 24 and 36 months than in those aged 3 and 6 months. Goats aged 9 and 12 months had significantly higher texture scores than those aged 3, 6, and 36 months. Overall, our findings suggest that goats aged 9 and 12 months exhibit the best sensory qualities.